The Effect of Diet Propolis Supplementation on Ross Broiler Chicks Performance - Shalmany, S. Khojasteh; Shivazad, M. (International Journal of Poultry Science, 2005)
An experiment was conducted to investigate the effects of Alcoholic Extract of Propolis (AEP) on Ross (308) broiler chicks performance. This experiment , was carried out in a completely randomized design with 6 treatments (different levels of propolis including 0, 50, 100, 150, 200 and 250 mg/kg diet) for 6 weeks. Weight gain, feed consumption , feed conversion ratio and mortality rate at the end of 3rd, 6th wk and whole periods (0 to 6 wk ) were compared statistically. Results indicated that in all periods, average weight gain, feed consumption, feed efficiency were significantly higher for propolis fed birds and inclusion of Propolis also reduced mortality rate in comparison to control diet.